2019
DOI: 10.1096/fj.201902203rr
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CCL2 contributes to BBB disruption via the p38 MAPK signaling pathway following acute intracerebral hemorrhage

Abstract: Intracerebral hemorrhage (ICH) remains a devastating type of stroke that lacks an effective treatment. Recent evidence has demonstrated that CCL2 is involved in the blood‐brain barrier (BBB) disruption and propagermanium (PG) as a CCL2 receptor inhibitor is neuroprotective in ischemic stroke. However, whether PG therapy exert effective role in acute ICH still unclear. In this study, our goal was to investigate the potential role of CCL2 and the effects of PG in ICH. Differentially expressed RNAs including CCL2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 36 publications
0
49
0
1
Order By: Relevance
“…However, CCL-2 was significantly less induced in the TLR4 mut mice compared with the TLR4 WT mice at days 4 and 6 PI, but was induced to similar levels at day 8 PI (Figure 3d). CCL-2 attracts monocytes and T cells as well as contributes to BBB permeability [33]. The reduced inductions of MMP-9, MMP-2, CCL-2 and ICAM-1 in the TLR4 mut mice support the role of TLR4 mediating BBB permeability during VEEV infection.…”
Section: Impaired Tlr4 Signaling Reduces the Upregulation Of Bbb Permeability-related Proteins During Veev Tc-83 Infectionmentioning
confidence: 61%
“…However, CCL-2 was significantly less induced in the TLR4 mut mice compared with the TLR4 WT mice at days 4 and 6 PI, but was induced to similar levels at day 8 PI (Figure 3d). CCL-2 attracts monocytes and T cells as well as contributes to BBB permeability [33]. The reduced inductions of MMP-9, MMP-2, CCL-2 and ICAM-1 in the TLR4 mut mice support the role of TLR4 mediating BBB permeability during VEEV infection.…”
Section: Impaired Tlr4 Signaling Reduces the Upregulation Of Bbb Permeability-related Proteins During Veev Tc-83 Infectionmentioning
confidence: 61%
“…The human cerebral microvascular endothelial cell line hCMEC/D3 and a human astrocyte (HA) cell line were generous gifts from the Shenzhen Institutes of Advanced Technology, Chinese Academy of Sciences. A coculture model was developed in our previous study 11 . Three to four days after the initial coculture, S1P (1 µM, Apexbio, USA) and CAY10444 (1 µM, Glpbio, USA) were added to the endothelial side.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies found that, MAPK pathway can active FoxO family [25]. Interestingly, autocrine CCL2 is associated with activation MAPK pathway [26]. We next investigated the relationship between MAPK pathway and FoxO1 activity in response to rCCL2 stimulation in macrophage.…”
Section: Ccl2 Induces Foxo1 Activation Via P38 Mapk Pathway In Thp-1 mentioning
confidence: 95%